Twenty years of air pollutant index trend analysis in Kuching, Sarawak, Malaysia (2000-2019) - Siti Hasyyati Drahman,; Hisyammudin Maseri,; Maqueline Cyndi Nap,; Zetty Baiduri Hossen, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sarawak is expected to face environmental challenges due to air pollution arising from industrial emissions and urbanisation as it strives towards achieving developed and high-income status by 2030. Therefore, it is important to conduct a comprehensive Air Pollutant Index (API) trend analysis. There are currently limited studies on API trend analysis that focus on Kuching, the capital known for its extensive industrial zones and densely populated urban centre. The main focus of this study was to perform a comprehensive analysis of the API trends in the Kuching region over a period of 20 years (2000-2019) using a visual representation in the form of a contour plot. To achieve this purpose, a five-term Fourier model was employed to predict the missing API data using Matlab software. Then, a complete version of a contour plot was developed to clearly illustrate the fluctuations in air quality over time. It was found that a five-term Fourier model used to forecast missing API data provides a strong correlation with the API readings, with most of the R values greater than 0.91. Moreover, the generated contour plot demonstrates a visual congruence between the forecasted data and the original dataset. Elevated API readings, signifying highly detrimental air quality, were primarily identified as a result of haze episodes stemming from uncontrolled fires in neighbouring countries, particularly during El Niño events. The findings of this study contribute to a better understanding of API trends in Kuching by means of the contour plot.